Physiological and morphological characterization of avocado creole (Persea americana Mill.) accessions for elite rootstocks - Bedoya-Ramírez, Sara Isabel; Saavedra-Porras, Susan; Loaiza-Ruíz, Ruby Alejandra; Barrera-Sánchez, Carlos Felipe; Córdoba-Gaona, Oscar de Jesús (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
The selection of a suitable cultivar as a seed source for rootstock production can be considered of great importance since the success or failure after the plantation establishment depends on the attributes of the material used as a pattern in the production of seedlings. This research aimed to characterize morphologically and physiologically different creole cultivars of avocado to identify elite materials that can be used as rootstocks. The research was carried out in Supia, Caldas - Colombia (5°26'39'' N; 75°38'56'' W). A completely randomized experimental design was used with 17 treatments (accessions) and 20 replications. The variables evaluated were rootstock stem diameter, rootstock height, leaves number, leaf area index (LAI), specific leaf area (SLA), dry matter, net photosynthesis (A), stomatal conductance (gs), transpiration (E), and water use efficiency (WUE). The largest records were for rootstock stem diameter ID08, ID-06 (˃ 9 mm), rootstock height ID01, ID-15 (˃ 60 cm), leaf area ID08 and ID15 (> 2000 cm2), LAI ID14 (1.99), SLA ID06 and ID17 (164.23 and 167.57), total dry matter ID01, ID08, ID15 (43.50, 42.91 and 42.80), A: ID01 and ID02 (˃6 μmol CO2 m-2 s-1), gs: ID-16 (0.15 mol H2O m-2 s-1), E: ID-16 (5.93 mmol H2O m-2 s-1) and WUE: ID02 (1.70 μmol CO2/mmol H2O) accessions. The origin of the avocado cultivars significantly influenced physiological and morphological behavior, thus enabling the detection of early attributes for selecting materials that can be used as rootstocks.